Germinated Brown rice enhanced n-3 PUFA metabolism in type 2 diabetes patients: A randomized controlled trial. Issue 4 (April 2023) - Na, Guanqiong; Zhang, Jing; Lv, Dian; Chen, Ping; Song, Xinyue; Cai, Fenfen; Zheng, Sicong; Wan, Wenting; Shan, Yujuan
Summary: Background: Brown rice (BR) has been considered as a potential strategy in improving T2DM. However, there are a lack of population-based trials on the association of Germinated brown rice (GBR) and diabetes. Aims: We aimed to explore the influence of GBR diet in T2DM patients for 3 months and whether this effect relates to serum fatty acids. Methods: Two hundred and twenty T2DM patients have been enrolled and eligible subjects (n = 112, 61 female, 51 male) were randomly divided into GBR intervention group (n = 56) and control group (n = 56). Except those who lost follow-up and withdrew, final GBR group and control group consisted of 42 and 43 patients, respectively. Participants in GBR group were asked to consume 100 g/d GBR instead of equal refined grain (RG) for 3 months, while control group maintain their usual eating habits. A structured questionnaire was used for demographic information at baseline, and basic indicators were measured both at the beginning and end of the trail to evaluate plasma glucose and lipids levels. Results: In GBR group, mean dietary inflammation index (DII) decreased, indicating GBR intervention retarded patient inflammation. Besides, glycolipid related parameters, including FBG, HbA1c, TC and HDL, were all significantly lower than those in control group. Excitingly, fatty acid composition was changed by intake of GBR, especially n-3 PUFA and n-3/n-6 PUFA rate were significantly increased. Moreover, subjects in GBR group had higher levels of n-3 metabolites, such as RVE, MaR1 and PD1, reducing inflammatory effect. In contrast, n-6 metabolites, like LTB4 and PGE2 which could promote inflammatory effect, were lower in GBR group. Conclusion: We confirmed that diet with 100 g/d GBR for 3 months could really improve T2DM to some extent. This beneficial effect may be related to n-3 metabolites, namely inflammation changes. Trial registration: ChiCRT-IOR-17013999, www.chictr.org.cn .